Long-term dynamics of the huge Anmangynda aufeis in the North-East of Russia (1962–2021) - A. A. Zemlianskova; V. R. Alekseev; A. N. Shikhov; A. A. Ostashov; N. V. Nesterova; O. M. Makarieva (Лëд и снег, 2023)
The huge Anmangynda aufeis is located in the valley of the river of the same name in the Magadan region in North-East of Russia. This is the only in the world aufeis site with a 30-years period of ground-based observations (1962–1991). The materials of these observations were supplemented with data obtained from the analysis of Landsat and Sentinel satellite images for the period 2000–2021, as well as the results of field investigations carried out in 2020–2021. The long-term variability of the maximum area, volume and average thickness of ice, the dynamics of formation and destruction of the aufeis ice in the cold and warm periods of the year were analyzed. It was found that the maximum values of the area and volume of ice on the dates before the start of ablation decreased by 25 and 33%, respectively. In 2000–2021, the average values of the aufeis characteristics are estimated as 4.7 km2 and 7.1 million m3, while in 1962–1991 – 5.5 km2 and 8.5 million m3. The analysis of the intra-annual dynamics revealed that the Anmangynda aufeis being earlier the perennial formation has transformed to the seasonal one. Further researches of the Anmangynda aufeis will make possible to assess the influence of various factors, including climatic ones, on the processes of an aufeis formation and to forecast their changes in the future for the cryolitic zone of the North-East of our country.